Comparison population of rat species composition in between Petaling Jaya and Subang Jaya with particular reference to on rattus rattus, rattus norvegicus and suncus murinus - Mohd Yusoff, Nor Syahirah (2017)
The increase in human population in urban center, rat is anticipated to increase in number tremendously the rapid development in urban areas and the increase in connectivity with the rural areas through movement of the human population and means of transportation, distribution of rat population and species composition may have changed. Therefore there is a need to survey the rat population in the cities. In the particular project, there is the particular interest to determine the rat species distribution so as to match with control method. The experimental initiative of using barn owl in the cities may requires a knowledge of the rat species in order to understand the prey preference of the former and its effectiveness in the respective rat control programme.. Specifically, the main objective of this study was to compare rodent species inselected urban areas i.e Subang Jaya and Petaling Jaya in Selangor. An additional investigation on ectoparasite identification of the respective rat species was carried out as comparison for similarities or differences as a result of difference in habitat preference. The area chosen for the study site was Subang Jaya and Petaling Jaya. The method employed in this study was removal method. Location of study on rattus species was conducted at two different places at Pasar Jalan Othman and Subang Jaya area to estimated population of rat in both area. Once rattus species have been capture, they were killed by using chloroform and their size, weight and sex were measured. The results of population density were analyses by using statistic method. The result of population density showed Rattus norvengicus are higher than Rattus rattus in both area. The finding of these study would contribute to a better understanding of rat ecology in urban area which is extensile for exobiological control.